Country Portrait Portugal - Belchior-Rocha, H.; Casquilho-Martins, I.; Figueiredo, V. (Socialnet International, 2020)
The country portraits/country profiles may be of interest for all who would like to gain a first substantial overview of the socio-political, socio-economic and social work-related situation in the respective countries. Be it in terms of professional peer-to-peer interaction, for explorers, student exchanges, public agencies or social enterprises. Furthermore the growing cross-border need for social care provision and the digital transformation increasingly call for international and transnational knowledge education.